Cardiopulmonary Resuscitation in Interfacility Transport: An International Report Using the Ground Air Medical Quality in Transport (GAMUT) Database. (10th July 2020) - Bhalala, Utpal S.; Srivastava, Neeraj; Gothard, M. David; Bigham, Michael T.
Abstract : Background . With the regionalization of specialty care, there is an increasing need for interfacility transport from local to regional hospitals. There are very limited data on rates of cardiopulmonary resuscitation (CPR) during medical transport and relationship between transport-specific factors, such as transport program type and need of CPR during transport of critically ill patients. We present the first, multicenter, international report of CPR during medical transport using the large Ground and Air Medical qUality Transport (GAMUT) database. Methods . We retrospectively reviewed the GAMUT database from January 2014 to March 2017 for CPR during transport. We determined the overall CPR rate and CPR rates for adult, pediatric, and neonatal transport programs. The rate of CPR per total transports was expressed as percentage, and then, Spearman's rho nonparametric associations were determined between CPR and other quality metrics tracked in the GAMUT database. Examples include advanced airway presence, waveform capnography usage, average mobilization time from the start of referral until en route, 1 st attempt intubation success rate, and DASH1A intubation success (definitive airway sans hypoxia/hypotension on 1 st attempt). Data were analyzed using chi-square tests, and in the presence of overall significance, post hoc Bonferroni adjusted z tests were performed. Results . There were 72 programs that had at least one CPR event during the study period. The overall CPR rate was 0.42% (777 CPR episodes/184, 272 patient contacts) from 115 programs reporting transport volume and CPR events from the GAMUT database during the study period. Adult, pediatric, and neonatal transport programs ( n = 57, 40 and 16, respectively) had significantly different CPR rates (P < 0.001 ) i.e., 0.68% (555/82, 094), 0.18% (138/76, 430), and 0.33% (73/21, 823), respectively. Presence of an advanced airway and mobilization time was significantly associated with CPR episodes (P < 0.001 ) (Rs = +0.41 and Rs = −0.60, respectively). Other transport quality metrics such as waveform capnography, first attempt intubation, and DASH1A success rate were not significantly associated with CPR episodes. Conclusion . The overall CPR rate during medical transport is 0.42%. Adult, pediatric, and neonatal program types have significantly different overall rates of CPR. Presence of advanced airway and mobilization time had an association with the rate of CPR during transport.